ANALISIS MANAJEMEN BISNIS SYARIAH STRATEGI PENANGANAN PEMBIAYAAN BERMASALAH PT. MITRA BUANA ASRI SENTOSA - Oviani, Ega; Thantawi, Tubagus Rifqy; Purnama , Bayu (Sahid Business Journal : Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
Financing has a very important role in banking whose main source of income is financial sector institutions. Financing can also become problematic if it is not reviewed properly and thoroughly by the financial institution, which will cause the financing to become problematic or stalled. This study uses a qualitative method. This research aims to determine the factors that can influence the occurrence of problematic financing and strategies for handling problematic financing at PT. Mitra Buana Asri Sentosa. Researchers conducted this research at PT Mitra Buana Asri Sentosa. Researchers used observation, interviews and documentation methods to collect data. The results of this research are the factors that cause financing problems, namely internal and external factors. Internal factors are caused by a consumer selection system that is not yet optimal, and there is no consistent application of sanctions. External factors that cause financing problems are a lack of goodwill from consumers and the Covid-19 virus which has implications for consumers' inability to make payments. Strategy for handling problematic financing at PT. Mitra Buana Asri Sentosa is carried out using preventive strategies and repressive strategies. The preventive strategy is carried out by implementing a more thorough and optimal selection system for potential consumers, determining costs for consumers who will make a return and carrying out an assessment or analysis of financing applications. The repressive strategy is carried out by means of intensive billing, the 3R program (rescheduling or rescheduling, reconditioning or returning requirements, and restructuring or restructuring) and proposing a return or refund scheme. PT. Mitra Buana Mitra Asri Sentosa has relatively carried out sharia business management in Islam by including a balance of honor for parties or people who make it easier for people who are in debt, and for parties or people who prioritize repayment of their debts, in their internal regulations in the form of Procedures for Applying for Financing, and Strategy for Handling Financing Problems.